An all-optical single-step process for production of nanometric-sized fluorescent diamonds. Issue 12 (14th March 2018) - Basso, L.; Gorrini, F.; Cazzanelli, M.; Bazzanella, N.; Bifone, A.; Miotello, A.
Abstract : Nanodiamonds (NDs) containing negatively charged Nitrogen-Vacancy (NV) centers are promising materials for applications in photonics, quantum computing, and sensing of environmental parameters like temperature, strain and magnetic fields. Abstract : Nanodiamonds (NDs) containing negatively charged Nitrogen-Vacancy (NV) centers are promising materials for applications in photonics, quantum computing, and sensing of environmental parameters like temperature, strain and magnetic fields. However, the production of fluorescent NDs remains a technological challenge, requiring a complex multi-step process involving controlled introduction of substitutional nitrogen into the diamond lattice, annealing and fragmentation from macrocrystals to nanocrystals. Here, we report on a single-step, all-optical process for the production of nanometric-sized fluorescent diamonds based on laser ablation of a carbon substrate at low temperature (100 °C) under a nitrogen atmosphere. We demonstrate that this synthesis route yields fluorescent NDs with a concentration of native NV centers controlled by adjusting the experimental ablation conditions. Spin-polarization dependent optical-transitions are observed by optically detected magnetic resonance spectroscopy, thus providing strong evidence of the presence of negatively charged NV centers in the as-grown NDs. Finally, we propose a thermodynamic model able to describe the nucleation of NDs and the formation of NV centers in the present single-step optical process.